DEŞİK KLİNİK ÖRNEKLERDEN SOYUTLANAN KANDİDA TÜRLERİNE VİRULANS FAKTÖRLERİNDEN PROTEİNAZ, FOSFOLİPAZ VE ESTERAZ AKTİVİTELERİNİN ARAŞTIRILMASI - SOYDAN, SEVDA (Fırat Üniveristesi, 2005)
Kandidalar doğada, insan ve hayvanların florasında bulunan maya morfolojisinde mikroorganizmalardır. Son yıllarda kanser, transplant ve immunsüpresif hastaların yaşam süreleri, gelişmiş tedavi protokolleri nedeniyle uzamış ve dolayısıyla bu hastalarda mantar enfeksiyonu görülme sıklığı artmıştır. Mantar enfeksiyonlarında Candida albicans dışında diğer kandida türlerinin izolasyonundaki artış, bu türlerin virülans faktörlerinin önemini arttırmıştır. Enfeksiyon oluşumunda konak faktörleri kadar kandidaların virülans faktörleri de önemli bir yer tutmaktadır. Bu çalışmada, çeşitli klinik örneklerden izole edilen 100 kandida susunun türleri belirlenmiş ve türlere göre proteinaz, fosfolipaz ve esteraz aktiviteler: araştırılmıştır. 100 kandida susunun; 58' i C. albicans,14' ü C. glabrata, 11' C. tropicalis, 52' i C.famata, 4' ü C. sake, 3' ü C. knısei, 2' si C guillermondii, V C. lusiianiaee, l'i C. pelliculose, 1' i C. curvata olarak adlandırılmıştır. Proteinaz enzim aktivitesi, Sığır Serum Albumin Agar'da, protein lizisine bağlı olarak şeffaf zonlann oluşup oluşmamasına göre değerlendirilmiştir. Proteinaz oram türlere göre; % 82.7 C albicans, % 72.7 C. tropicalis, % 40 C.famata, % 50 C guillermondii, % 100 C. lusitaniae, % 100 C. curvata olarak tespit edilmiştir. C sake, C. krusei ve C. pelliculose de proteinaz aktivitesi görülmemiştir. Proteniaz aktivitesinin kilinik örneklere göre dağılımı ise, dışkı, boğaz, balgam, yara % 100, kan % 83.3, vaginal akıntı % 57.9, idrar % 46.6 olarak değerlendirilmiştir. Fosfolipaz enzim aktivitesi, Yumurta Sanlı Agar besiyerinde değerlendirilmiştir. Koloni çapının, koloni ve presipitasyon zonunun uzunluğuna oranlanarak, l'-e eşit olanlar olumsuz, l'den küçük olanlar olumlu olarakdeğerlendirilmiş ve türlere göre C. albicans % 89.6, Ctropicalis % 72.7 olarak bulunmuştur. Diğer türlerde fosfolipaz aktivitesi görülmemiştir. Klinik örneklere göre ise, boğaz % 100, kan ve idrar % 66.6, vaginal akıntı % 59.4 oranında fosfolipaz aktivitesi tespit edilmiştir. Esteraz aktivitesi Tween 80 Ağarda, inokülasyon bölgesinin etrafında ışığı geçiren opak kristaller veya opak alan oluşumu gözlenenler olumlu, gözlenmeyenler olumsuz olarak değerlendirilmiştir. Türlere göre C. albicans %93.1, C. tropicalis % 100, C. glabrata % 7.1, C. famata %60, G guillermondii %50, C. curvata % 100, olarak tespit edilmiştir. Diğer türlerde esteraz aktivitesi gözlenmemiştir. Klinik örneklere göre esteraz aktivitesi, dışkı, boğaz, balgam ve yarada % 100, vaginal akıntıda % 73.9, kanda % 66.6, idrarda % 53.3 oranında tespit edilmiştir. Sonuç olarak, kandidalarda virülans faktörlerinden olan proteinaz,fosfolipaz ve esteraz üretimi sıklığı, çalışmamızda izole edilen suşlar arasında orta ve üst düzeyde saptanmış olup, kandida enfeksiyonlarında bu enzimlerin araştırılması, tedavinin planlanmasında yaralı olacaktır. Anahtar kelimeler : Kandida türleri, proteinaz, fosfolipaz, esteraz..

Determination of the Proteinase, Phospholipase and Esterase Activity Among the Candida Strains Isolated From Various Clink Samples Candidas are the yeast which can be found free in nature or in the various microbial flora of human and mammalian animals. In recent years, the patients', with cancer, transplant and receiving immunosuppressive therapy, life expectancy has been increased due to developed therapy protocols. The increasing isolation rates of non-albicans strains from the yeast infections, caused to augment of the medical importance of the virulence factors of these strains. Virulence factors of Candida contribute to develop infection as much as the host's factors. In this study, species determinations were performed of a total of 100 Candida strains and proteinase, phospholipase and esterase activity according to species were investigated. Of the total 100 Candida strains, 58 were found as Candida albicans, 14 were C. glabrata, 1 1 were C. tropicalis, five were C. tropicalis, four were C.famata, four were C. sake, three were C. krusei, two were C. guiellermondii, one was C. lusitaniaee, one was C. pelluculosa and one was C. curvata. Proteinase activity was investigated in bovine serum albumin agar according to visualize translucent area due to protein lysis. Proteinase rate according to species were; 82.7 % for C. albicans, 72.7 % for C. tropicalis, 40 % for C. famata, 50 % for C. guillermondii, 100 % C. lusitaniaee and for C. cruvata. No proteinase activity detected in C. sake, C. krusei and C. pelluculosa strains. The distribution of the proteinase activity according to clinic samples were; 100% for stool, nasopharynx,sputum and wound; 83.3 % for blood, 57.9 % for vaginal discharge and 46.6 % for urine. The phospholipase activity was investigated in agar with egg's allontois media. The radius of the Candida's colony was divided to length of the colony plus precipitation zone diameter. In the case of the rate was 1, it was commenced as negative; smaller than 1 ones were accepted as positive reaction. According to species rates were found as; 89.6 % for C. albicans, 72.7 for C. tropicalis. There was no phospholipase activity in the other species. The distribution of the phospholipase activity according to clinic samples were; 100 % for nasopharynx, 66.6 % for blood and urine sputum and 59.4 % for vaginal discharge. The esterase activity was investigated in Tween-80 agar. In the inoculation area; collection of the translucent opaque crystals or emerging opaque zones were indicated that the esterase production. Esterase production rate according to species were; 93.1 % for C. albicans, 100 % for C. tropicalis, 7.1 % for C. glabrata, 60 % for C.famata, 50 % C. guillermondii and 100 % C. cruvata. There was no esterase activity in the other species. The distribution of the esterase activity according to clinic samples were; 100 % for stool, nasopharynx, sputum and wound; 73.9 for vaginal discharge, 66.6 % for blood and 53.3 % for urine. Among the Candida strains that were included in to the study, proteinase, phospholipase and esterase production rates, as the virulence factors of Candida species, were found in moderate to high levels and in the case of Candida infections, investigation of the production of these factors will contribute to planning the therapy. Keywords: Candida strains, proteinase, phospholipase, esterase.
Determination of the proteinase, phosphlipase and esterase activity among the candida strains isolated from various clinic samples
Keywords: Mikrobiyoloji